2019
DOI: 10.2478/tekhne-2019-0014
|View full text |Cite
|
Sign up to set email alerts
|

A Content Analysis on the Small and Medium-Sized Enterprises in the United States of America

Abstract: The present research was constructed with the idea of offering a detailed view on one of the most important legislative papers of the United States of America (USA), namely, the Small Business Act of 1953. The public policy sector in the USA is a rather complex area of research, and the qualitative study performed through the content analysis has been based on external factors within the Small Business Administration (SBA) for the small and medium-sized enterprise (SME) sector in the USA, in terms of financial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In the Western world, studies [3] showed that there is a connection between the managerial styles and leadership strategies within Canadian SMEs, and the commitment of the latter towards ethical and sustainable practices. The US small and mediumsized enterprises are regulated through the Small Business Act, and includes information on the facilitation of technology transfers, involvement and aid of minority entrepreneurs, shared production facilities, access to online data, reduction in the use of paper [12]. The European Union is probably the main focus of the research on ethics and sustainability in the SME sector, with papers referring to subjects such as the implementation of responsible research and innovation (RRI) within the SME public policy for the development of ethical and sustainable activities and organizational frameworks [2], andsetting standards that promote innovation and effective corporate reporting, as well as creating the perfect hub for experimentation [4] in an ethical, globalized world.…”
Section: Problem Statementmentioning
confidence: 99%
“…In the Western world, studies [3] showed that there is a connection between the managerial styles and leadership strategies within Canadian SMEs, and the commitment of the latter towards ethical and sustainable practices. The US small and mediumsized enterprises are regulated through the Small Business Act, and includes information on the facilitation of technology transfers, involvement and aid of minority entrepreneurs, shared production facilities, access to online data, reduction in the use of paper [12]. The European Union is probably the main focus of the research on ethics and sustainability in the SME sector, with papers referring to subjects such as the implementation of responsible research and innovation (RRI) within the SME public policy for the development of ethical and sustainable activities and organizational frameworks [2], andsetting standards that promote innovation and effective corporate reporting, as well as creating the perfect hub for experimentation [4] in an ethical, globalized world.…”
Section: Problem Statementmentioning
confidence: 99%
“…For members of OECD, SMEs account for more than 97% of the total number of firms. In the U.S., for instance, SMEs create 75% of the country's additional annual employment opportunities and employ nearly 50% of the private labor force, signifying 99.7% of total employers (Grigorescu & Ion, 2019). The success of SMEs is highly attributed to its simple arrangement, their speedy reaction to economic conditions and their ability to satisfy the needs of local clients, sometimes expanding to large and influential companies or failing within a short span from its commencement.…”
mentioning
confidence: 99%